The Nuit Blanche Pavilion; Using the Elasticity of Polymers for a Lightweight Structure. (September 2013) - Riether, Gernot
The Nuit Blanche Pavilion is a recent project by Gernot Riether in collaboration with artist Damien Valero. The project takes advantage of an elastic behavior found in high-density elastomers to form a lightweight structure that integrates form, geometry and program in a single material system. Grasshopper and the finite element plug-in Karamba were used to optimize these interdependencies. This paper will describe the design of the project and elaborate on an aspect of Riether's research that uses digital technology to promote environmentally responsible materials and construction methods.